Cardiotonic Activity of Coconut Water (Cocos nucifera) - M. Ramesh, C.H. Praneeth Sagar, U. Bhaskar Rao, G. Lakshman, M. Ankaiah, J. Balu Naik, Hemanth Sairam Pattigadapa (Recent Research in Science and Technology, 2011)
The coconut (Cocos nucifera) is a member of the family Arecaceae (Palm family). Various parts of this tree is used in the treatment of, cancer (due to hexane fraction of coconut peel), indomethacin-induced ulceration (coconut milk).Coconut water consumption reduces diastolic blood pressure (due to the presence of potassium).In the present work fresh coconut water, dilution 1:1(coconut water: distilled water), are used to evaluate cardiac activity on the isolated frog heart and are labeled as T1, & T2 respectively and compared with Digoxin (S1) as standard solution. It was found that sample T1(Undiluted coconut water) showed better response as compared to the diluted coconut water(T2).These preliminary studies confirm the cardiotonic activity of the coconut water(Cocos nucifera).